Design, Synthesis, and Insecticidal Activity of Novel Pyrazole Derivatives Containing α-Hydroxymethyl-N-benzyl Carboxamide, α-Chloromethyl-N-benzyl Carboxamide, and 4,5-Dihydrooxazole Moieties - Song, Hongjian; Liu, Yuxiu; Xiong, Lixia; Li, Yongqiang; Yang, Na; Wang, Qingmin (Journal of agricultural and food chemistry, 2012)
On the basis of commercial insecticides tebufenpyrad and tolfenpyrad, two series of novel pyrazole-5-carboxamides containing α-hydroxymethyl-N-benzyl or α-chloromethyl-N-benzyl and pyrazoles containing 4,5-dihydrooxazole moieties were designed and synthesized via the key intermediate 2-amino-1-(4-substituted) phenyl ethanol. The structures of target compounds were confirmed by 1H NMR and elemental analysis or high-resolution mass spectrum (HRMS), and their activities against cotton bollworm (Helicoverpa armigera), diamondback moth (Plutella xylostella), bean aphid (Aphis craccivora), mosquito (Culex pipiens pallens), and spider mite (Tetranychus cinnabarinus) were tested. The results of bioassays indicated that compounds containing α-chloromethyl-N-benzyl and compounds containing 4,5-dihydrooxazole showed high insecticidal activity against cotton bollworm. Especially, stomach activities of compounds Ij, Il, and IIe were 60% at 5 mg kg–1. Moreover, the target compounds exhibited high selectivity between cotton bollworm and diamondback moth, although both of them belong to the order Lepidoptera. Although the activities against diamondback moth were at a low level, some of the target compounds exhibited antifeedant activity. The compounds also had good activities against bean aphid, mosquito, and spider mite. The foliar contact activity of compounds Ic, Id, Ie, and IIf against bean aphid were 95, 95, 100, and 95%, respectively, at 200 mg kg–1. The miticidal and ovicidal activities of compound IIi against spider mite were both 95% at 200 mg kg–1. Furthermore, a trivial change at 4-position of pyrazole ring would lead to great changes in properties and activities, which can easily be deduced by comparing the activities of compounds in series I (4-chloro-pyrazole compounds) with corresponding compounds in series II (4-hydro-pyrazole compounds), especially from the miticidal and ovicidal activities of Ii and IIi against spider mite.